Analysis of the Relationship between Technology Awareness and Career Opportunities in Metland Tourism Vocational High School Students - Nurul Sukma Lestari; Dendy Rosman; Farah Levyta (Kontigensi : Jurnal Ilmiah Manajemen, 2021)
With the industrial revolution 4.0, the use of advanced technology based on artificial intelligence has begun to be implemented by business people in the tourism industry, especially in the hotel sector. Although it has many advantages, the use of Robots, AI, Service Automation (RAISA) also impacts employees, one of which is the fear of losing opportunities and job opportunities. Therefore, this study examines the relationship between awareness of the use of RAISA and perceptions of future career opportunities. This research focuses on Vocational High School (SMK) students because they are potential workers in this industry in the future. This study uses quantitative methods. 247 SMK students participated in this research by filling out a survey questionnaire that was distributed to them. This study found a positive and significant relationship between awareness of RAISA and perceptions of future career opportunities. The study results are expected to contribute to the literature in the field of human resource management.